Strain behavior and lattice dynamics in Ni50Mn35In15 - Mejia, C. Salazar; Nayak, A. K.; Schiemer, J. A.; Felser, Claudia; Nicklas, Michael; Carpenter, M. A. (Journal of Physics: Condensed Matter, 2015)
The lattice dynamics in the polycrystalline shape-memory Heusler alloy Ni50Mn35In15 have been studied by means of resonant ultrasound spectroscopy (RUS). RUS spectra were collected in a frequency range 100-1200 kHz between 10 and 350 K. Ni50Mn35In15 exhibits a ferromagnetic transition at 313 K in the austenite phase and a martensitic transition at 248 K accompanied by a change of the magnetic state. Furthermore it displays a paramagnetic to ferrimagnetic transition within the martensitic phase. We determined the temperature dependence of the shear modulus and the acoustic attenuation of Ni50Mn35In15 and compared it with magnetization data. Following the structural softening, which accompanies the martensitic transition as a pretransitional phenomenon, a strong stiffening of the lattice is observed at the martensitic magneto-structural transition. Only a weak magnetoelastic coupling is evidenced at the Curie temperatures both in austenite and martensite phases. The large acoustic damping in the martensitic phase compared with the austenitic phase reflects the motion of the twin walls, which freezes out in the low temperature region.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Heusler alloys; martensitic transition; resonant ultrasound spectroscopy